A imprensa feminista e suas contribuições para pensar a educação - Souza, Giovanna Gabriela Cavalcante de (Universidade Federal de São Carlos, 2021)
This study aims to analyze the use of feminist graphic humor present in Ciça’s comic strips published and released in feminist newspapers "Brasil Mulher", "Nós Mulheres" and "Mulherio" between 1975 and 1987, during a civil and military dictatorship in addition to the emergence of feminist movements in their second wave. Through cartoons and comic strips - understood as discourses - that integrate these periodicals, I try to understand how humor with a feminist perspective can be understood and used for the education of women, who since its beginning - thinking of colony Brazil - was authoritarian and practically inaccessible. Throughout this work, I try to identify, through the description and analysis of the graphic humor present in daily life of the character “Bia Sabiá”, indications that demonstrate the potential of the feminist media as an instrument of education for women to become aware of their human condition in a patriarchal society. The research, in its methodological organization, is of a qualitative, bibliographic and documentary nature. It is worth mentioning that, using humor and laughter, the present newspapers are characterized by a particular approach, by the context in which they were published and, especially, in the treatment of cultural, social, political and economic elements, as well as the understanding public and private policy.
The feminist press and its contributions to think education
Keywords: Mídia; Educação; Feminismo; Periódicos Feministas; Educação Feminina; Media; Education; Feminism; Feminist Newspapers; Education for Women; CIENCIAS HUMANAS::EDUCACAO